On Quasi-ω-Confluent Mappings - Abdo Qahis; Mohd. Salmi Md. Noorani (International Journal of Mathematics and Mathematical Sciences)
We introduce a new class of mappings called quasi-ω-confluent maps, and we study the relation between these mappings, and some other forms of confluent maps. Moreover, we prove several results about some operations on quasi-ω-confluent mappings such as: composition, factorization, pullbacks, and products.